2021
DOI: 10.21595/jve.2020.21635
|View full text |Cite
|
Sign up to set email alerts
|

Induction motor pre-excitation starting based on vector control with flux linkage deviation decoupling

Abstract: The traditional starting methods for induction motors are easy to cause excessive starting current, which causes serious damage to AC speed regulating system. With analysis on the essence of magnetic field control, A method on asynchronous motor pre-excitation starting based on flux linkage compensation deviation decoupling is proposed in this paper. Based on vector control, a DC flux linkage with stable amplitude and direction is established by using DC pre-excitation starting method. According to the fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Based on the essence of magnetic field control, Cao et al scholars achieved smooth motor starting by vector control and establishing a flux chain that can ensure stable amplitude and direction. The results indicated that this method effectively reduced peak current and had good application performance [14].…”
Section: Related Workmentioning
confidence: 92%
“…Based on the essence of magnetic field control, Cao et al scholars achieved smooth motor starting by vector control and establishing a flux chain that can ensure stable amplitude and direction. The results indicated that this method effectively reduced peak current and had good application performance [14].…”
Section: Related Workmentioning
confidence: 92%
“…It is urgent to consider increasing the technical requirements such as primary frequency modulation and highvoltage ride through capacity of wind farms. At the same time, the technical terms such as grid adaptability and lowvoltage ride through capacity also need to be modified and improved [7] .…”
Section: Virtual Inertia Control Of Variable Speed Wind Turbinementioning
confidence: 99%
“…Other equipment used to improve the energy performance of an asynchronous electric drive during start-up includes devices that allow adjusting the voltage at the motor terminals, and, accordingly, controlling the start and stop of the drive, and provide energy savings by reducing the voltage on an underloaded motor [20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%